Development of Teaching Materials for Writing Short Story Texts Based on the KBM (Community Can Write) Application by Asma Nadia and Isa Alamsyah in Creative Thinking Skills for Junior High School Students - Anita Rizkiyanti; Saifur Rahman; Fathiaty Murtadho (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to develop and evaluate a short story writing instructional material based on the "Komunitas Bisa Menulis" (KBM) application using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. This instructional material is designed to improve students' short story writing skills and creative thinking through an interactive technology-based approach. The development process involved analyzing the needs of students and teachers, designing technology-based content, and testing by subject matter and media experts. The implementation was carried out in several pilot classes using both online and offline methods, and evaluation was conducted using sebelum tess and setelah tess to measure students' skill improvement. The results of the trial showed a significant improvement in students' short story writing skills (35%) and creative thinking skills (40%). This study provides evidence that the instructional material based on the KBM application is effective in enhancing students' short story writing and creative thinking skills.